Adsorption Of Clomid Drug On Activated Carbon And Zinc Oxide Surfaces (Journal of the College of Basic Education, 2023)
The research included study the adsorption of Clomid drug on thesurface of activated carbon and zinc oxide. Many of parameters werestudied which affect the adsorption process such as temperature, weight ofadsorbent, equilibrium time, initial concentration and effect of pH.Activated carbon and zinc oxide were used as a model adsorbent in theexperiments. We found that increased of temperature (30-50) °C followedby increased in adsorption capacity experiments were done at 30 °C andshowed that the optimum weight of activated carbon was (0.15 g) while forzinc oxide was (0.1g), equilibrium time was (150 min) for the twoadsorbents. The adsorption capacity of the two adsorbents increased withincreasing initial concentration of drug, In addition, the experimentsshowed that the (3-7) pH was the best medium of the adsorption process.